Kostium historyczny jako narzędzie manifestacji postaw religijnych i światopoglądowych łódzkich Żydów w latach 1892-1919 na przykładzie wybranych nagrobków z cmentarza żydowskiego w Łodzi - Gadowska, Irmina (Studia Europaea Gnesnensia, 2015)
Stratification of the cemetery’s space reflects the social structure of the city, revealing an internal hierarchy, the worldview and the tastes of the inhabitants. The message that a headstone conveys is a resultant of the communication intended by those who commissioned it and the historical context. The means of visual expression, as well as the nature of the embellishments are the necessary tools for its reading. This text is concerned with the possibilities of analysing and interpreting historical forms found at the Jewish cemetery in Łódź, taking into account the time when they were created, the location, the patron and the historical context.